Evaluation of Antimicrobial and Wound Healing Effects of Gold Nanoparticles Containing Abelmoschus esculentus (L.) Aqueous Extract - Shahla Korani; Khodabakhsh Rashidi; Mona Hamelian; Ali R. Jalalvand; Ahmad Tajehmiri; Mitra Korani; Thozhukat Sathyapalan; Amirhossein Sahebkar (Bioinorganic Chemistry and Applications)
Background. Wound healing is a complex process of replacing devitalized cellular structures and tissues with healthy cells and tissue. Nanotechnology has been increasingly proposed as a novel platform to treat wounds and skin regeneration. The aim of this study was to evaluate the antibacterial, antioxidant, cytotoxic, and cutaneous wound healing activities of phytosynthesized Au NPs using Abelmoschus esculentus (okra) and synthesized Au NPs by using the citrate synthesis method. The Ok Au NPs were characterized using various techniques like UV-Vis absorption spectroscopy, FTIR, X-ray diffraction (XRD), and transmission electron microscopy (TEM). Cutaneous wounds were created on 30 rats and randomized into three groups: untreated and two groups treated with Ch Au NPs and Ok Au NPs. The treatment was carried out daily for 12 days. A peak characterized the Ok Au NPs at 538 nm in the UV-Vis spectrum. Based on the results of FTIR spectroscopy, various functional oxygenated groups such as hydroxyl, carboxyl, and nitrogenous groups were observed. XRD confirmed the crystalline nature of the nanoparticles. TEM images of Ok Au NPs showed a spherical shape and size range of 75 nm. DPPH test showed similar antioxidant potentials for Au NPs. The Au NPs showed cell viability in a dose-dependent manner, and this technique was found to be nontoxic. Agar well diffusion, which is the method to determine antibacterial characteristics of Au NPs, showed a significant beneficial effect against a variety of bacterial species. In addition, histopathological results showed that Au NPs could accelerate wound closure. Therefore, Au NPs could be suitable for wound healing applications.